Art For Morals’ Sake Or The Other Way Around : moral concerns in Oscar Wilde’s aestheticism - Candeias, Francisco (2021)
Oscar Wilde’s concerns with ethics and morals seldom dominate discussions around his work, which often focus on his role as a leading English aesthete and on his remarkable appetence for witticism. Such concerns, however, permeate his oeuvre quite extensively and offer a new perspective through which his critical theory might be perceived. The equilibrium achieved between Wilde’s most flagrante remarks about literary criticism and his underlying belief that art could add something to life and society have secured him a distinct place in the history of world literature that should not be overlooked.